Simultaneous analysis of sixteen energetic nitro compounds and their degradation products in groundwaters and surface waters by ultra-high-performance liquid chromatography - Alen Albreht; Anja Koroša (Environmental Chemistry and Ecotoxicology)
An analytical method based on ultra-high-performance liquid chromatography with photodiode array detection for the simultaneous separation and determination of nitroaromatics, nitramines, and nitrate esters in aqueous environmental samples was developed. The modification of a preconcentration step based on solid phase extraction proved crucial for avoiding the frequently occurring measurement bias. The fully validated method has a range spanning four orders of magnitude and enables a precise, accurate, and sensitive determination of species down to a concentration of 0.3 μg/L. The method's applicability was demonstrated by quantifying energetic materials and their degradation products in nine groundwater and nine surface water samples, obtained from a single sampling campaign of Slovenian aquifers. Three contaminants, namely 1,3-dinitrobenzene (1,3-DNB), 2-amino-2,6-dinitrotoluene (2A-DNT), or pentaerythritol tetranitrate (PETN), were detected in 5 of the 18 samples. The measured concentrations of nitro compounds were low, with the exception of the Mura River, where PETN exceeded 1 μg/L. The anthropogenic origin of the pollution observed for this part of Europe must be linked to the (un)exploded ordnance from both World Wars. However, the presence of 1,3-DNB and 2A-DNT in the Pivka River is also likely to be associated with regular military activities in the area.